#TITLE_ALTERNATIVE# - PRASETYA PUTRA K. (NIM : 10511073), ANGGRIAWAN
Sea water has similar composition for its general structural components. However, in some locations has different composition because of industrial activities, fishermen, and the locals. The chosen sample location is Marunda Beach, Sunda Kelapa Harbor, and Ancol Beach. For that reason, the purpose of thi research is to analyze the existence of diazinon pestiside compound and polysiclic aromatic hydrocarbon (PAH) from sea water located at Jakarta's beach. The order of this research begins with sea water filtering, sample vaporization, and its residue is taken to be analyzed using Fourier transform infra red (FTIR), and determination of contents of diazinon pestiside compound and polycylic aromatic hydrocarbon naphtalene and anthracene from sample with high performance liquid chromatography (HPLC) method. The result with FTIR analysis shows that sample contains organic compund functional groups as alkyl halide (C-Halide), carbonyl (C=O), hydroxy (O-H), and aliphatic amines (R-NH2) from result of sample vaporization and drying by oven for 4 hours at 60 Ã‚Â°C. After that, analysis of diazinon pestiside compound and polycyclic aromatic hydrocarbon naphtalene and anthracene is done with reversed phase HPLC method and solid phase extraction. The election of wavelength in HPLC analysis is based on each diazinon standard solvent's maximum absorption, naphtalene, and anthracene obtained from maximum absorption test with spectrophotometer UV-Vis. Measurement result with HPLC method shows that there is peak chromatogram. Marunda Beach samples at retention time of 3.821 minutes is identified as diazinon compound with concentration of 7.37 ppm and 3.208 minutes is identified as naphtalene compound with concentration of 4.24 ppm. Next, at Sunda Kelapa Harbour samples at at retention time of 2.911 minutes is identified as naphtalene compound with concentration of 5.67 ppm and 5.326 minutes is identified as anthracene compound with concentration of 3.62 ppm. Instead, at Ancol Beach samples at retention time of 2.913 minutes is identified as naphtalene compound with concentration of 0.67 ppm and 5.349 minutes is identified as anthracene compound with concentration of 7.56 ppm. Supporting parameters in this reasearch is a pH of Marunda Beach, Sunda Kelapa Harbour, and Ancol Beach are 8.370, 8.323, and 8.362 respectively. In addition to pH, conductivity values are determined also from the third row of the sample, 82.2 ms, 82.4 ms and 82.9 ms.